2008
DOI: 10.1002/hlca.200890152
|View full text |Cite
|
Sign up to set email alerts
|

The Orthogonal (e,e,e)‐Tris‐Adduct of 9,10‐Dimethylanthracene with C60‐Fullerene: A Hidden Cornerstone of Fullerene Chemistry. Preliminary Communication

Abstract: Tris(9',10]ethanoanthracene [11',12': 1,9;11'',12'': 16,17;11''',12''': 30,31]) [5,6]fullerene C 60 , the orthogonal (e,e,e)-tris-adduct of C 60 and 9,10-dimethylanthracene, was obtained from [4 þ 2]-cycloaddition (Diels -Alder reaction) at room temperature. The thermally unstable orange red (e,e,e)-tris-adduct was purified by chromatography and was isolated in the form of red monoclinic crystals. Its C 3 -symmetric addition pattern was established spectroscopically. Its structure could be further investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
0
16
1
Order By: Relevance
“…Although the 1 H NMR studies in solution may not be directly applicable to the solid bulk material, those measurements are still useful for understanding of the time scale in relation to DA reaction conversion. Due to the highly reversible system, the final conversion within the bulk materials was uncertain.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…Although the 1 H NMR studies in solution may not be directly applicable to the solid bulk material, those measurements are still useful for understanding of the time scale in relation to DA reaction conversion. Due to the highly reversible system, the final conversion within the bulk materials was uncertain.…”
Section: Resultscontrasting
confidence: 62%
“…reported a DA cycloaddition of a bis‐ anthracene ester with C 60 ‐fullerene in the solid state by mechanochemical preparation and investigated a dissociation in the temperature range 40–65 °C. Kräutler and coworkers investigated intensively the formation of mono‐ and bis‐ adducts in the solid state and solution as well as the formation of different regioisomers and the decomposition reaction. Moreover, the authors reported the instability of the bis‐ and tris‐ adducts resulting in rapid rDA reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported the crystal structure of a pentakisadduct with an incomplete octahedral addition pattern and Chronakis and co‐workers published the structure of a trisadduct with e edge , e face , trans ‐ 1 ‐geometry 17. An e , e , e ‐tris‐dimethylanthracene adduct was the only other fullerene derivative with an e , e , e ‐addition pattern that was crystallized to date 18. The single crystals of the P in ‐isomer 18 were grown from hot [D 8 ]toluene solution.…”
Section: Methodsmentioning
confidence: 99%
“…54,56 The time-dependent measurements were performed as follows: first two spectra were recorded at ambient temperature. All Raman spectra contained slight contaminations of anthracene, which stems from the unavoidable degradation of the Diels-Alder adducts.…”
Section: Ft-raman Measurementsmentioning
confidence: 99%